Gynecologic oncology clinical practice and surgical atlas - Karlan, Beth Y. q (Beth Young); Bristow, Robert E.; Li, Andrew J. (McGraw-Hill, 2012)
"Essential Gynecologic Oncology will be the most comprehensive single resource on the topic. Currently, all texts in the field present either a medical discussion or surgical procedures. Available surgical atlases are either terribly outdated or shockingly expensive. EGO will be the first to combine these two kinds of resources in a single affordable volume. Each topic is written by experts and is presented in an easily accessible consistent presentation that highlights clinical practice guidelines along with the diagnosis and treatment of specific malignancies. This authoritative coverage is reinforced by the state of the art surgical atlas which offers a richly illustrated, overview of essential procedures designed to build your knowledge and confidence"--Provided by publisher.